Developing a Core Outcome Set for the Evaluation of Antibiotic Use in Prelabor Rupture of Membranes: A Systematic Review and Semi-Structured Interview - Liu, Dan; Wu, Lin; Luo, Jiefeng; Li, Siyu; Liu, Yan; Zhang, Chuan; Zeng, Linan; Yu, Qin; Zhang, Lingli (Frontiers in Pharmacology, 2022)
Background: Prelabor rupture of membranes (PROM) is associated with maternal and neonatal infections. Although guidelines suggest prophylactic antibiotics for pregnant women with PROM, the optimal antibiotic regimen remains controversial. Synthesizing the data from different studies is challenging due to variations in reported outcomes. Objective: This study aimed to form the initial list of outcomes for the core outcome set (COS) that evaluates antibiotic use in PROM by identifying all existing outcomes and patients’ views. Methods: Relevant studies were identified by searching PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure, Wanfang, and VIP databases. We also screened the references of the included studies as a supplementary search. We extracted basic information from the articles and the outcomes. Two reviewers independently selected the studies, extracted the data, extracted the outcomes, and grouped them into domains. Then, semi-structured interviews based on the potential factors collected by the systematic review were conducted at West China Second Hospital of Sichuan University. Pregnant women who met the diagnostic criteria for PROM were enrolled. Participants reported their concerns about the outcomes. Two researchers identified the pregnant women’s concerns. Results: A total of 90 studies were enrolled in this systematic review. The median outcomes in the included studies was 7 (1–31), and 109 different unique outcomes were identified. Pre-term PROM (PPROM) had 97 outcomes, and term PROM (TPROM) had 70 outcomes. The classification and order of the core outcome domains of PPROM and TPROM were consistent. The physiological domain was the most common for PPROM and TPROM outcomes. Furthermore, 35.1 and 57.1% outcomes were only reported once in PPROM and TPROM studies, respectively. Thirty pregnant women participated in the semi-structured interviews; 10 outcomes were extracted after normalized, and the outcomes were reported in the systematic review. However, studies rarely reported pregnant women’s concerns. Conclusion: There was considerable inconsistency in outcomes selection and reporting in studies about antibiotics in PROM. An initial core outcomes set for antibiotics in PROM was formed.